Studi Perancangan Mesin Pencacah Cokelat Kapasitas Produksi 600Kg/Jam dengan Metode VDI 2222 - Riona Ihsan Media; Bustami Ibrahim (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2019)
This article discusses the design process of a chocolate crusher machine based on VDI 2222. The design activities begin with identifying the needs and demands of the customer until finishing the solution for the customer in the form of a design work drawing in technical documentation. The proposed method is validated in a case study of making a chocolate chopper machine design. The machine generally functions as a separator between the cocoa beans and the shell of the seeds which have been chopped in such a way as to produce the required dimensions. At the planning stage, identifying the machine's need is to be able to chop the cocoa beans until the smallest grain has a maximum dimension of 4 mm. Three alternative functions are given and assessed as a result of the conceptualization stage. Evaluation is given to the draft design by considering the material, manufacturing and maintenance aspects. At the completion stage, technical documentation in the form of detailed work drawings is produced. By setting the rotating speed, a chocolate crusher can make beans with dimensions of 2-4 mm and production capacity is about 600 kg/hour.